2019
DOI: 10.1007/s10901-019-09675-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing university students' accommodation choices: risk perception, safety, and vulnerability

Abstract: Students'mobililty has grown considerably in the last decades and student housing has recently started to be studied more consistently, because of the high pressure on the private market. However, its implication for policy making and societal resilience remains a marginal topic in the scientific debate and further studies are needed to meet the goals of the Sendai Framework for Disaster Risk Reduction. Students could be seen as a vulnerable category to be considered to understand and reduce disaster risk, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…With the growing volumes of student mobilities within the IHES framework, one pertinent ethical implication is the security and wellbeing of international students. Issues of vulnerability and needs, including international students’ emotional challenges, have been discussed thoroughly in previous studies (Brown and Jones, 2013; Magni et al, 2019; Poyrazli and Lopez, 2007). Forbes-Mewett (2016), in her analysis of the accounts of professionals in Australia who worked with full degree and short-term international students, highlights the significant rise in the number of students experiencing stress and emotional problems.…”
Section: Ethical Implications Of Student Mobilities and What Our Study Has Highlightedmentioning
confidence: 99%
“…With the growing volumes of student mobilities within the IHES framework, one pertinent ethical implication is the security and wellbeing of international students. Issues of vulnerability and needs, including international students’ emotional challenges, have been discussed thoroughly in previous studies (Brown and Jones, 2013; Magni et al, 2019; Poyrazli and Lopez, 2007). Forbes-Mewett (2016), in her analysis of the accounts of professionals in Australia who worked with full degree and short-term international students, highlights the significant rise in the number of students experiencing stress and emotional problems.…”
Section: Ethical Implications Of Student Mobilities and What Our Study Has Highlightedmentioning
confidence: 99%
“…Even though students' high education level, good health, and renter status make them more resilient to disasters, on the other hand, their lack of experience, financial and emotional dependence on their families can make them more vulnerable (Simms et al, 2013). The fact that students from other cities or countries are unaware of the city's institutions, risk and safety awareness, and social structure make them more vulnerable to disasters (Magni, Pescaroli, & Bartolucci, 2019). On the contrary, scientific studies have shown that students' disaster preparedness and mitigation situations are quite low (Lovekamp & Tate 2008;Tanner & Doberstein, 2015;Wu et al, 2017).…”
Section: Disasters and Studentmentioning
confidence: 99%
“…Apartments that are convenient to a person's daily destinations are leasing well (J Turner Research, 2016). One study found that college students choose housing based primarily on rental price (Magni et al, 2019).…”
Section: Apartment Livingmentioning
confidence: 99%
“…Trending among apartment complexes is the development of common areas that are similar to resorts in terms of atmosphere and services provided. In addition to providing computers and coffee stations, there may be a concierge or classes on cooking (Magni et al, 2019). Outside common areas are prevalent with lounge seating, grills and cabanas.…”
Section: Apartment Livingmentioning
confidence: 99%
See 1 more Smart Citation